2019
DOI: 10.33549/physiolres.934010
|View full text |Cite
|
Sign up to set email alerts
|

Tempol Alleviates Chronic Intermittent Hypoxia-Induced Pancreatic Injury Through Repressing Inflammation and Apoptosis

Abstract: Obstructive sleep apnea (OSA) has been demonstrated to be implicated in disorder of insulin secretion and diabetes mellitus. In this study, we aimed to evaluate the protective role of tempol, a powerful antioxidant, in chronic intermittent hypoxia (IH)-induced pancreatic injury. The rat model of OSA was established by IH exposure. The pathological changes, increased blood-glucose level, and raised proinsulin/insulin ratio in pancreatic tissues of rats received IH were effectively relieved by tempol delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 33 publications
0
26
1
1
Order By: Relevance
“…Tempol has been shown to protect cells and tissues from oxidative damage 21 , 23 26 . In contrast, it has also been reported that Tempol enhances inflammation and oxidative damage in numerous cell and tissue models 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tempol has been shown to protect cells and tissues from oxidative damage 21 , 23 26 . In contrast, it has also been reported that Tempol enhances inflammation and oxidative damage in numerous cell and tissue models 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Tempol is a potential redox agent that may function as a reductive or oxidative mediator depending on its concentration in the cell 21 . Treatment with Tempol removes a variety of ROS and diminishes oxidation, subsequently protecting cells and tissues from oxidative injuries 21 , 23 26 . Our previous reports have shown that Tempol prevents lung cancer cells and juxtaglomerular cells from undergoing cell death in response to cytotoxic insult 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Bax/Bcl-2 as well as cleaved-caspase-3/caspase-3 are critical markers of apoptosis. The former promotes apoptosis, while the latter inhibits apoptosis and they regulate apoptosis by controlling the permeability of mitochondrial membranes (33). In addition, the Bcl-2 gene can regulate the activity of cleaved-caspase-3, which eventually leads to apoptotic cascade (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Tempol has been shown to protect cells and tissues from oxidative damage [23][24][25][26][27] . In contrast, it has also been reported that Tempol enhances in ammation and oxidative damage in numerous cell and tissue models 21,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Tempol is a potential redox agent that may function as a reductive or oxidative mediator depending on its concentration in the cell 21 . Treatment with Tempol removes a variety of ROS and diminishes oxidation, subsequently protecting cells and tissues from oxidative injuries [23][24][25][26][27] . Our previous reports have shown that Tempol prevents lung cancer cells and juxtaglomerular cells from undergoing cell death in response to cytotoxic insult 28,29 .…”
Section: Introductionmentioning
confidence: 99%